2013
DOI: 10.1111/febs.12105
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cell‐free protein synthesis for the crystallization of membrane proteins – a case study on a member of the glutamate transporter family from Staphylothermus marinus

Abstract: Cell‐free in vitro synthesis of proteins using coupled transcription/translation is considered to be a powerful alternative to the use of traditional cell‐based expression systems. Recently, promising developments have been reported applying cell‐free production to membrane proteins for structural biology and in particular for NMR spectroscopy. However, the general applicability of this system to produce large amounts of stable, functional and homogeneous membrane proteins as required for X‐ray crystallography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…The cell-free methods are expected to become the standard procedures for crystallography-oriented membrane protein preparation, as they overcome a number of difficulties that unavoidably accompany the cell-based recombinant expression methods with respect to the preparation of mammalian membrane proteins. These expectations have been mentioned previously 38 39 , but have not been met successfully in the crystallography of mammalian membrane proteins at atomic resolution. In this study, we applied the P-MF and S-MF methods to the cell-free protein production and purification of mammalian α-helical membrane proteins.…”
Section: Discussionmentioning
confidence: 91%
“…The cell-free methods are expected to become the standard procedures for crystallography-oriented membrane protein preparation, as they overcome a number of difficulties that unavoidably accompany the cell-based recombinant expression methods with respect to the preparation of mammalian membrane proteins. These expectations have been mentioned previously 38 39 , but have not been met successfully in the crystallography of mammalian membrane proteins at atomic resolution. In this study, we applied the P-MF and S-MF methods to the cell-free protein production and purification of mammalian α-helical membrane proteins.…”
Section: Discussionmentioning
confidence: 91%
“…To investigate whether our in vitro subunit reassembly procedure is applicable to other multimeric transporters, we initially tested the procedure on Glt Sm , a glutamate transporter homolog from Staphylothermus marinus that shares 58% sequence identity to Glt Ph ( Figure 5A )( Jaehme and Michel, 2013 ). We observed that SDS dissociated the Glt Sm transporter and that the dissociated subunits can be reassembled back to the trimeric state upon dilution of SDS coupled with protein incorporation into lipid vesicles ( Figure 5B ).…”
Section: Resultsmentioning
confidence: 99%
“…Glt Sm was amplified by PCR from a plasmid carrying the gene for a Glt Sm -GFP fusion protein ( Jaehme and Michel, 2013 ) and cloned into a pBAD-HisA vector (Fisher Scientific) with a N-terminal His 6 tag. The Glt Sm vector was transformed into TOP10 cells (Fisher Scientific) for protein expression.…”
Section: Methodsmentioning
confidence: 99%
“…The alternate technology that eliminates most of these drawbacks is cell‐free in vitro protein synthesis. Presently, only a few crystallography groups have employed this technology to prepare soluble proteins and, recently, membrane proteins . In the case of RNAs as well, specific drawbacks have to be overcome for the preparation of homogeneous samples for crystallization.…”
Section: Crystallogenesis In the Era Of Technologies And Structural Gmentioning
confidence: 99%